Kontroversi Perempuan Sebagai Wali Nikah - Najib, Agus Moh. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
The concept of waliin marriage contract is essentially a mean to ascertain the attainment of the goal of a marriage, that is to maintain harmony between a husband and wife in their familial life. The institution of wali (guardianship) is meant to guarantee the rights, safety and welfare of the underage brides before and after they enter their marital life. Thus, it can be said that wali for a brU1e is needed when she is not adult yet, and has no capability to conduct legal acts by herself Meanwhile a waliwho is meant to be her protector should be an adult person with sound judgment and ability to perform legal acts so that the wali can perform the duties appropriately. If the main condition of wali is adulthood and soundness of judgment, then women, not only men, can be a wali, as it is believed by the Hanafis.